2003
DOI: 10.1021/ol035373u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Reported Structure of Pogostol and a Total Synthesis of (±)-Kessane without the Use of Protecting Groups

Abstract: [reaction: see text] A short racemic synthesis of kessane from 4-hydroxy-4-methyl-2-cyclohexenone is described using a route that also resulted in the synthesis of the reported structure of pogostol. The key step involves an Fe(III)-mediated tandem radical ring-expansion/cyclization of the cyclopropylsilyl ether 9. No protecting groups are used in the entire sequence. Comparison of the NMR data of synthetic pogostol to that in the literature indicates that the structure originally proposed is incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…For 118 this discussion is hypothetical, because this compound was only obtained in racemic form by synthesis and is not known as natural product. [299] The hydrocarbons( + +)-115 and( + +)-116 were both isolated only from the fruits of Peucedanum tauricum. [311] Their co-occurrencei no ne organisms uggests that they may have the same cationic precursor J3.T he absolute configurations of 115 and 116 were specified by comparison of their hydrogenation products to those obtained from (+ +)-g-gurjunene (120, Scheme 30 B), [312] leading to one common product (119a)f rom all three materials, as judged by GC analysisu sing two different chiral stationary phases.…”
Section: Guaianes Formedf Romcationsj3a Nd J4mentioning
confidence: 99%
See 1 more Smart Citation
“…For 118 this discussion is hypothetical, because this compound was only obtained in racemic form by synthesis and is not known as natural product. [299] The hydrocarbons( + +)-115 and( + +)-116 were both isolated only from the fruits of Peucedanum tauricum. [311] Their co-occurrencei no ne organisms uggests that they may have the same cationic precursor J3.T he absolute configurations of 115 and 116 were specified by comparison of their hydrogenation products to those obtained from (+ +)-g-gurjunene (120, Scheme 30 B), [312] leading to one common product (119a)f rom all three materials, as judged by GC analysisu sing two different chiral stationary phases.…”
Section: Guaianes Formedf Romcationsj3a Nd J4mentioning
confidence: 99%
“…[293] As ubsequent synthesis of the reported structures 104 and 105 for pogostol and its methyl ether demonstrated that both assignments were erroneous. [299] Amand et al then gave ac orrection as 103. [295] Althoughp ogostoli sl ong known and fairly widespreadi n Nature,t he absolutec onfigurations till remains to be determined.F or unclear reasons the structure of ent-103 has been assigned to the CAS number of pogostol (21698-41-9), while in fact 103 may be more likely, because this corresponds to the main product 106 of the patchoulol synthasef rom P. cablin that also makes 103 as as ide product.…”
Section: Guaianes Formed Fromcationsj1a Nd J2mentioning
confidence: 99%
“…In the same year the structures for pogostol and its methyl ether were challenged by Booker‐Milburn et al after their total synthesis . On the basis of 13 C‐NMR data, they proved that natural pogostol was neither identical to H nor to its 7‐epimer.…”
Section: Analytical Investigations Of Patchouli Essential Oilmentioning
confidence: 99%
“…Unfortunately, published mass spectra and retention indices for all other stereoisomers of pogostol and of globulol were not available, so these compounds were also candidate structures for X . The 13 C NMR data for all five compounds1620 and the two pogostol stereoisomers ( 11 and 12 )21 have been reported, and therefore we strived to confirm the identities of X and 10 by obtaining 13 C NMR data for X by CLSA‐NMR (note: the originally published structure of 10 22 was later found to be incorrect21 and then corrected;23 in ref. 17 the wrong structure is shown for 13 ).…”
Section: Methodsmentioning
confidence: 99%